PENGARUH PEMBERIAN EDUKASI TERHADAP SIKAP IBU HAMIL TENTANG CARA MENGATASI MUAL MUNTAH PADA TRIMESTER 1 DI PUSKESMAS CONDONG: The Effect of Giving Education Toward The Behavior of Pregnant Women About How to Overcome Nausea and Vomiting in the First Trimester at the Condong Health Center - Nur Kholifah Kholid (Forind Press, 2024)
Excessive nausea and vomiting is one of the complications of pregnancy that affects the health status of the mother and the growth and development of the fetus. If this nausea and vomiting occurs excessively, the nutritional intake of the fetus will be reduced which can cause impaired fetal growth. Based on a preliminary study at the Condong Health Center, there were 37 pregnant women who experienced nausea and vomiting, of whom 22 were unable to deal with nausea and vomiting properly. The purpose of this study was to provide education on how to deal with nausea and vomiting at the Condong Health Center in the hope that pregnant women can deal with nausea and vomiting in the right way. This study used the pre-experimental design method using the one group pretest and posttest design. Data collection was carried out by providing verbal education using leaflet media on how to deal with nausea and vomiting in pregnant women. Then the data was processed by a two-sample T-test using SPSS assistance. From the results of calculating the statistical test Paired Sample T-Test using SPSS showed a significant number between the pre- and post-test values with a significance value (2-tailed) p = 0.000, ≤ 0.05 where the alternative hypothesis (Ha) was accepted which means that there is an effect of providing education on attitudes of pregnant women about how to deal with nausea and vomiting in the first trimester at the Condong Health Center.